Study on the role of albendazole in physiological and histological changes in farm chicken infected with environmental parasites in Dawmat AlJandal, AlJouf, Saudia Arabia Kingdom: Albendazole on physiological and histological changes - Hamza, Hanan; Al-Namasi, Aziza; Al-Ruwaili, Fanar; Al-Shammari, Hoda; Aly, Ibrahim (WAS Science Nature (WASSN) ISSN: 2766-7715, 2024)
Background: Farm birds, or chickens, are susceptible to a variety of parasite infections that are spread by people. The anti-parasitic medication of choice is albendazole (ABZ). This article's main objective is to examine the effects of ABZ on the intestine and hepatic tissue of farm hens. Methods: ABZ recorded an egg reduction rate (ERR) of almost 100% and a cure rate (CR) of 96% (egg negative conversion rate, or NCR) with 400 mg given all at once. A total of 20 farm chickens were divided into 4 groups (5 chickens/ group): (G1) non-infected, untreated group, (G2) infected, untreated group, (G3) is non-infected ABZ-treated group, and (G4) is infected ABZ-treated group. Results: Regarding the average number of worms (Ascaris) (G2) and (G4) recovered from the gut increased significantly (P<0.01). While there was a significant decrease in the average number of worms (G4) (25%) compared to those infected only (48%). The results obtained also showed a highly significant increase (P<0.05) in the average number of worms in the intestines among the infected group. (Hymenolipes) (G2) (41%), while there was a significant decrease in the average number of worms (G4) (17.3%) compared to those infected only. AST levels showed a significant increase in groups (G2) and (G4) compared to the normal control group. The percentage increase reached 124.65% and 256.33%, respectively at P<0.001 and P<0.01. While (G3) treated with albendazole recorded a decrease rate of 51.85%. AST levels in the plasma of groups (G3) and (G4) recorded a significant increase compared to the infected control group (G2) .An increase in ALT was recorded in groups (G2) compared to the control group (G1). The percentage increase reached 127%. An increase in ALT was recorded in groups (G2) and (G4) compared to the normal group (G1). The percentage increase reached 127% and 48.03%, respectively. The histological study of both the liver and intestines demonstrated the pathological effect of the tissues treated with albendazole, and on the contrary, the treatment affected the decrease in the number of worms in the intestines. Conclusions: The study indicates that treatment with albendazole for chickens infected with various parasites led to a decrease in the number of worms. It also led to an increase in the values of liver enzymes and also some abnormalities in both the liver and intestines.